Hubungan pemanfaatan dana bantuan operasional kesehatan (BOK) dengan peningkatan cakupan kunjungan antenatal K4 di puskesmas kota Serang tahun 2014-2016 (Berita Kedokteran Masyarakat (BKM), 2018)
Relation between health operational aid fund (BOK) with increase in K4 antenatal visiti scope at Serang city community health centers year 2014-2016Health Operational Aid Fund (BOK) realization at Serang City Community Health Centers (CHC) through 2014-2016 has always reached 100% mark which more than 30% of the fund was allocated for maternal and children health each year. However the achievement from maternal and children health scope especially on K4 antenatal visit was not proportional with the budget, instead each year a decreasing trend from proposed target (75%) was observed thus the need of evaluation. This study was conducted at regional health agency and four CHCs (Banten Girang, Curug, Sawah Luhur and Serang Kota) with retrospective study case design and considering fund variables and scopes. The result shows lack of human and other resources in managing maternal and children health program; the lack of operational fund for preventive and promotive activities from regional government budget (APBD) and only rely on health operational fund; the lack of supervision in midwife records and reports, also the contract ending of trained cadres as the result of village chief replacement.